Evaluasi Efektivitas Teknologi Internet of Things untuk Deteksi Dini Risiko Kebakaran dan Paparan Gas Berbahaya di Kamar Mesin Kapal - Muhammad Saleh (Journal of Artificial Intelligence and Technology Information (JAITI), 2026)
Ship engine rooms are high-risk working environments due to the presence of fuel, lubricating oil, hot surfaces, electrical installations, and potential exposure to hazardous gases. This study aimed to evaluate the effectiveness of Internet of Things (IoT) technology in supporting the early detection of fire risks and hazardous gas exposure based on crew experience, and to identify the technical, human, environmental, and organizational factors affecting its implementation. This study employed a qualitative approach with an evaluative case study design. Data were collected from 85 purposively selected informants through in-depth interviews, observations of 85 units, and documentation. The data were analyzed thematically, while their validity was strengthened through source and technique triangulation. The findings indicate that IoT is sufficiently effective in supporting continuous monitoring, accelerating warning delivery, identifying hazard types and locations, and facilitating the crew’s initial response. Observations showed that 91.8% of units had fire and/or hazardous gas sensors, 90.6% of devices were functional and in good condition, 85.9% of systems clearly displayed hazard types and locations, 88.2% had maintenance or calibration records, and 94.1% demonstrated crew readiness to respond to alarms. However, effectiveness remained suboptimal because of false alarms, connectivity disruptions, transmission delays, unclear information, engine-room environmental conditions, and varying crew competencies. It is concluded that IoT is an effective detection and decision-support system but cannot replace direct inspection and professional judgment. Improved effectiveness requires marine-grade devices, risk-based sensor placement, scheduled maintenance, backup communication, regular training, clear procedures, and integration with the ship’s Safety Management System to enhance early-warning reliability and prevent hazardous conditions from developing into shipboard accidents.